Long-term follow-up of patients in the TIght COntrol of inflammation in early Psoriatic Arthritis (TICOPA) trial. (31st August 2019) - Coates, Laura C; Mahmood, Farrouq; Freeston, Jane; Emery, Paul; Conaghan, Philip G; Helliwell, Philip S
Abstract: Objectives: The TIght COntrol of inflammation in early Psoriatic Arthritis (TICOPA) study was the first strategy trial in psoriatic arthritis using an early treat-to-target strategy to improve clinical outcomes. The current study aimed to review a cohort of patients who had completed TICOPA to judge if the clinical advantage gained by participants in the tight control (TC) arm was sustained, and to explore subsequent therapy. Methods: A case note review was conducted for a cohort of patients who had participated in TICOPA. Current drug use and clinical status were obtained, with low disease activity judged as no tender or swollen joints, no dactylitis and enthesitis, and no change in treatment required. Results: Approximately five years after completion of the TICOPA study, notes were reviewed for 110 patients [TC, n = 54; standard care (StdC), n = 56]. Disease activity was found to be similar in both groups (current low disease activity: TC 69%, StdC 76%). Biologic use at the end of the study was higher in the TC arm (TC 33%, StdC 9%), but at review a similar percentage in both groups were taking biologic drugs (TC 54%, StdC 52%), whereas MTX use diminished. Conclusion: After several years, clinical outcomes and therapeutic drug use were similarly good for patients in both arms of the TICOPA study, with no obvious clinical advantage after TC ended. Notably, TC did not result in greater biological use long term, and MTX use decreased in both arms of the study.